Modeling a conceptual proposal to analyze psychosocial characteristics of Peruvian social entrepreneurs - Vera Ruiz, Angela (2020)
Objective: This study aims to propose a comprehensive approach to five theoretical dimensions, characteristic of social entrepreneurs, to design a conceptual model that analyzes them based on macro-level psychosocial constructs such as beliefs and practices. Method: A qualitative study was conducted with 16 social entrepreneurs from the city of Lima (Peru). Using a deductive thematic analysis, their careers were examined and made operative based on their beliefs and/or practices, and on more specific psychosocial variables such as values, attitudes, behaviors and traits. Results: The attitudinal dimension of Positive Attitudes Towards Sustainable Practices (PASP) is the articulating main point in which all participants’ experiences come together to define their social vision, of axiological nature, promoting competent behaviors including innovation, networks and financial returns. Conclusion: The results highlight the need to deepen the study of the PASP dimension focused on the Peruvian social issues.   Authorship Contribution AVR: coordination, conception and design of the study, data collection, coding and analysis of information, theoretical argumentation, main writing of the manuscript and final revision of the document. MAPV: design and development of the instrument, contact with participants, data collection, theoretical argumentation and document revision. AEP: theoretical development of conceptual model, design and development of the instrument, and review of final theoretical discussion. EFNL: literature review, construction of theoretical argumentation for the discussion of results and review of formal aspects for presentation of the manuscript.